Austeritätspolitik in Estland: die Reaktionen der Wähler auf die Genommene Sparmassnhamen Während der Finanz – und Wirtschaftskrise 2008-2011 - Kulu, Liina; Veebel, Viljar (Estonian Discussions on Economic Policy, 2014)
During the latest global financial crisis, austerity as a concept has been described as the best possible and inevitable solution to achieve fiscal consolidation in Europe and in the euro zone. But even considering austerity as an economically rational measure, the politicians of most EU member states’ have introduced the austerity measures only to a limited extent or have chosen less stressful and politically less risky strategies. Estonian politicians, having earlier shock therapy experience from the years of re-independence, were among few European governments, who decided to adopt austerity measures with its economic and social consequences. Against all theoretical and rhetorical expectations they remained in power. The aim of the article is to analyze why austerity has not triggered negative political reaction of citizens, as expected in theoretical models as well feared by politicians, and was it caused by specific socio-cultural factors or well-planned strategy of government